Perception of consumers toward Islamic banking products and services: a case study in Segamat, Johor / Nurul Ain Hazirah Azmi - Azmi, Nurul Ain Hazirah (Faculty of Business Management, 2017)
This research attempted to investigate the perception of consumers toward Islamic banking products and services in Segamat, Johor. The research conducted by questionnaire method as the primary data, which the data for the research collected through a questionnaire survey of people that live the area of Segamat City, Johor. In this research, 156 respondents carried out as a sample of customers who hold bank account in conventional bank or Islamic bank. Perception of banking is a dependent variable meanwhile bank image, selection of bank and potential of Islamic banking are independent variable in this research. The result of analysis will be obtain.through research using Statistical Package for Social Science (SPSS) software for interpreting data. Furthermore, Google use to search supporting document or related journal and article which is secondary data to support this research. So that it can be concluded that all the independent variables have significant relationship between dependent variable, which is perception of banking and independents variable, which are bank image, selection of bank and potential of Islamic banking.